Gamma irradiation induced surface plasmon resonance of Cu nanoparticles in fullerene C60. (30th July 2022) - Bhardwaj, Jyotsna; Vishnoi, Ritu; Salim, Amena; Yadav, Shriniwas; Ojha, Sunil; Dwivedi, Umesh; Kandasami, Asokan; Kumar, Pushpendra; Sharma, Ghanshyam Dutt; Singhal, Rahul
Abstract : The present study reports the gamma irradiation‐induced surface plasmon resonance (SPR) of Cu nanoparticles (Cu‐NPs) that are embedded in the C60 fullerene matrix. These films were deposited by the thermal co‐evaporation technique. In this study, the fullerene C60 and CuC60 nanocomposite thin films were deposited separately and irradiated using gamma rays at various doses from 250 to 1000 kGy. A broad but well‐defined SPR peak is observed at approximately 618 nm after gamma irradiation at a dose of 1000 kGy as confirmed by UV–visible spectroscopy. An enhancement in the growth of Cu‐NPs with an average diameter of 46.05 nm is obtained at a dose of 1000 kGy. Raman spectroscopy confirms the ordering of fullerene C60 after gamma irradiation. However, the current–voltage measurements show that the resistivity of thin films remains approximately the same even after the highest doses of gamma irradiation. The electronic structures of these nanocomposite thin films were analyzed by X‐ray photoelectron spectroscopy. The incorporation of Cu‐NPs in fullerene C60 changes the nature of the surface from hydrophilic to hydrophobic. These results are understood based on the ionizing nature of the gamma rays.